Mythification of Development and Mystification of Culture: Ethnodevelopment as an Alternative - Palenzuela Chamorro, Pablo (2009)
This article has two objectives. The first is to reveal the ideological content that has become part of the concept of development. Whether it originates from academia or from the “developmentalist complex”, this ideology has led to the essentialist mystification of the notion of development, to the point of becoming a dogma in the narrative of modernity. The second challenge is to critically examine the ethnocentric relationship between development and culture in the hegemonic model of development. Its aim is to clarify the limits and possibilities of ethnodevelopment as an alternative.